Phosphorus-containing amorphous pure organic room-temperature phosphorescent materials. (5th December 2020) - Li, Zitong; Liu, Xiaoqin; Sun, Linbing; Ma, Xiang
Graphical abstract: Abstract: Amorphous organic room temperature phosphorescent (RTP) materials have attracted widespread attention due to their wonderful properties such as facile processability and good repeatability. Based on the existing design principles, embedding heteroatom-contained phosphors into rigid polymer matrices is a convenient way to construct high-efficiency amorphous RTP materials. In addition, phosphorus (P)-containing amorphous RTP materials are seldom seen to be reported. In this work, four amorphous polymers (P1-P4) containing P atoms have been successfully developed, which all could emit room-temperature phosphorescence but vary from each other under ultraviolet radiation. The phosphorescence was attributed to the lone-pair-electron-contained P atom which is favorable for n–π* transitions that leads to effective spin–orbit coupling and high ISC rate (kISC ) thereby enhances RTP in this system. Meanwhile, the hydrogen bonding effect is also necessary because it could enhance the conformation rigidification result in the reducing of the non-radiative decay. This study would enrich the amorphous pure organic RTP systems, and could be useful to provide thoughts for designing superior materials.